Penerapan Konsep E-Commerce melalui Strategi Pemasaran Digital pada UMKM Mom n Me di Desa Lhok Mambang, Aceh - Muttaqim, Hakim; Fauzi; Rizkina, Azka; Rizal, Muhammad (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The partner in this community service activity is the micro, small, and medium enterprise (MSME) Mom N Me, which specializes in the production of traditional Acehnese motif bags. This enterprise is located in Lhok Mambang Village, Gandapura District, Bireuen Regency, Aceh Province. Established in 2011, this MSME initially engaged in the sewing of ordinary clothing. In 2015, it began producing bags with distinctive traditional Acehnese motifs. However, since the onset of the COVID-19 pandemic, the sales of its products have declined due to the traditional marketing methods employed and the lack of appropriate technology in production. To elevate the MSME's performance, it is essential to train them in digital marketing to expand their market reach. The method employed in this community service involves training and hands-on practice. The outcomes of this activity include an enhanced understanding of digital marketing among MSME practitioners, a broader market reach, and increased revenue for the MSME.